L-shaped correlation between serum alpha-1-acid glycoprotein concentration and urinary albumin creatinine ratio in females: a cross-sectional survey - Wang, Junjie; Xiao, Li; Zhang, Yuxuan; Li, Zhou (Frontiers in Endocrinology, 2025)
BackgroundAlpha-1-acid glycoprotein (AGP) is a vital acute phase reactant that increases when glomerular filtration is impaired, making it a potential biomarker of kidney disease. The urine albumin-to-creatinine ratio (UACR) is a sensitive indicator of proteinuria and is frequently used to screen for kidney disease in its early stage. The aim of this study was to explore their correlation in order to advance our understanding of the mechanisms underlying kidney damage.MethodsThis study included 2579 female participants with serum AGP and UACR from the National Health and Nutrition Examination Survey (2015-2018). We divided all participants equally into three groups based on their serum AGP concentration. The univariate and multivariate regression models were for assessing the correlation between AGP and UACR. Subgroup analyses were then performed to explore the effect of each covariate on the correlation. Smoothing splines was utilized to explore their nonlinear correlation and identify thresholds within it.ResultsAfter adjusting for multivariate models, AGP was significantly and positively associated with UACR (p<0.0001). The study identified a specific cohort of non-Hispanic Black individuals under 20 years of age, characterized by a BMI below 25 kg/m² and a waist circumference of 80 cm or more. Within this cohort, those with hypertension and sleep disorders but without hypercholesterolemia or diabetes exhibited significantly higher UACR (p < 0.001). Furthermore, we discovered an L-shaped correlation between serum AGP concentration and UACR. Specifically, when the serum AGP concentration was less than 140 mg/dL, the UACR plateaued.ConclusionsThis study is the first to address the correlation between serum AGP and UACR and found an L-shaped correlation with a threshold of 140 mg/dl. This could be a target for intervention to reduce the risk of kidney disease.